Naturalna wolność i sztuczna władza - Fabiś, Piotr (Człowiek i Społeczeństwo, 2025)
The political theory presented by Hobbes in Leviathan is constructed around the opposition between Naturall and Artificiall. When the state does not exist, man finds himself in the condition of Nature. On the other hand, the state is Leviathan, which is Artificiall Man. When the state does not exist, only the Law of Nature applies. When the state exists, there are also artificial chains, which are state laws. This article contains an analysis highlighting this binary dimension of Hobbes’ theory and seeking to indicate the place occupied by the concepts of Liberty and Power in this theory. The analysis is supplemented by comments on the way Power is presented in the frontispiece of the 1651 London editions of Leviathan and the symbol of Liberty present in every classical western film.